The Susceptibility of katG Ser315Thr Mycobacterium tuberculosis mutant Against Anti Tuberculosis Drugs - Ning Rintiswati; P. Praseno (Universitas Gadjah Mada, 2014)
Mycobacterium tuberculosis resistant strains is a matter of great concern for TB control Program since nocure for some multi drug resistance TB (MDR-TB) cases. These strains could spread around the world, makea great challenges for control measures. Mycobacterium tuberculosis strains resistance to anti tuberculosis drugsis mainly caused by the alteration in several genes encoding the molecular targets. Mutation of katG at codon315 especially Ser315Thr are responsible for INH resistance in a large proportion of TB cases. The aim of thisstudy is to know the frequency of of katG Ser315Thr of M. tuberculosis mutant and the pattern of resistance toAnti TB drugs. The study design was observational laboratoric. Eighty fi ve M. tuberculosis INH resistant clinicalisolates were screened for mutation of katGSer315Thr by using PCR-RFLP and DNA sequence analysis.Theresults showed that katG Ser 315Thr were identifi ed in 23 (27,05%) of INH resistance isolates. Frequency ofMDR among the katG Ser315Thr mutants almost double than the non mutant. The result suggested that thethe katG Ser315Thr mutation may play important role in the development of MDR-TB.